Evaluasi Program Stunting di Kota Surakarta: Analisis Kinerja TK-KPM dan Efektivitas Program - Agustyarum Pradiska Budi; Wahyu Ratri Sukmaningsih; Deby Davista; Shavitri Chandriani; Aryawan Eka Syahputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims at the effectiveness of the stunting alleviation program and the performance of the Human Development Cadre Coordination Team (TK-KPM) in Surakarta City, using collaboration as a mediating variable. The variables studied include HR competency, government regulations, program implementation, information technology infrastructure, collaboration, program effectiveness, and time performance. The quantitative model used reveals that collaboration has quite good predictive power with an R-Square value of 0.644 and a Q-Square of 0.523. Collaboration is significantly influenced by HR competency, program implementation, and IT infrastructure. However, collaboration was not proven to be an effective mediator for program effectiveness (R-Square 0.029; Q-Square -0.002) or team performance (R-Square 0.438; Q-Square 0.193), where all related hypotheses were rejected. These results indicate that although collaboration can be strengthened through improving competence, infrastructure and program implementation, the impact on effectiveness and performance is not significant. These findings recommend developing more effective collaboration structures, optimizing HR competencies in teamwork, and strengthening information technology infrastructure that supports cross-sector communication. Further evaluation is also recommended to understand additional, more relevant factors, such as local policy support and incentives. The results of this research provide insight for the Surakarta City government to develop more targeted policies in supporting the TK-KPM team to increase the effectiveness and performance of the stunting alleviation program in a sustainable manner.